2014
DOI: 10.1109/tap.2014.2327653
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Dual-Polarized Printed Dipole Antenna With High Isolation for Wideband Base Station Applications

Abstract: A novel compact wideband dual-polarized printed dipole antenna for base station application is presented. The proposed antenna is composed of four assembled substrates. Two pairs of identical arrow-shaped conductive lines on the tophat substrate form two orthogonal polarized dipoles. Two baluns connected with 50 Ω coaxial cables are integrated on another two vertical substrates to excite the dipoles. The other horizontal board at bottom provides grounding. A rectangular box-shaped reflector is also used to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(100 citation statements)
references
References 10 publications
1
91
0
Order By: Relevance
“…In order to further broaden the AR bandwidth, two coplanar parasitic strips are introduced. The Z‐shaped dipole antenna is simply fed by a printed balun, which is usually used to feed dual‐polarized dipole antenna to achieve balanced feeding and wideband impedance matching. A prototype of the CP antenna has been fabricated and tested.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further broaden the AR bandwidth, two coplanar parasitic strips are introduced. The Z‐shaped dipole antenna is simply fed by a printed balun, which is usually used to feed dual‐polarized dipole antenna to achieve balanced feeding and wideband impedance matching. A prototype of the CP antenna has been fabricated and tested.…”
Section: Introductionmentioning
confidence: 99%
“…But a complex feeding network is indispensable when an antenna array is used as the excitation to feed the FPRA instead of a simple antenna. In consequence, choosing a simple feeding source with satisfactory performances, as the proposed antenna in [2] and giving the suitable design on PRS structure, are what antenna engineers should do. Some 1-D EBG resonator antennas with two layers dielectric slabs or multilayer superstrates as PRS achieved a 30% 3-dB gain bandwidth which was notable [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical height of these printed dipole antennas usually exceeds 0.25λ 0 (λ 0 is the free-space wavelength at the central operating frequency), and the transverse overall length exceeds 0.5λ 0 , which makes it difficult to be deployed in a size limited antenna application, e.g., multi-band side-by-side configuration or LSA, which requires even smaller adjacent spacing (0.5λ 0 Vs. 0.75λ 0 of conventional 10 • down tilt antenna) for the large 3D beamforming tilting range to achieve the boost of overall system's capacity. Recently, several compact wideband dipole antennas have been reported in [9][10][11]. Liu in [9] used a square patch director and an octagon ring as a parasitic element on top of the dual-polarized cross dipole to improve the bandwidth, as well as to achieve a size reduction.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a comparison on the transvers length L, physical height H and bandwidth of a printed dipole with integrated balun (antenna A) [6], a size-reduced printed dipole with triangular patch (antenna B) [11] and the proposed antenna C are listed in Table 1. It can be observed that all of them achieved wide impedance bandwidth over 40% (VSWR < 2).…”
Section: Introductionmentioning
confidence: 99%